2010
DOI: 10.1002/ctpp.201000071
|View full text |Cite
|
Sign up to set email alerts
|

Effective Polytropic Indices of Anisotropic Planetary Magnetosheath Plasmas with Magnetoacoustic Waves

Abstract: -adiabatic equation of state, magnetoacoustic waves, effective polytropic index, planetary magnetosheaths.Magnetosheath models for the planets Earth, Jupiter and Saturn are developed within the frame of the doubleadiabatic Chew-Goldberger-Low approximation. It is shown that in all three magnetosheaths slow and fast magnetoacoustic waves are generated, the dispersions of which considerably differ from that of isotropic systems. If slow magnetoacoustic waves exist in the magnetosheaths, then the effective polytr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…For example, the turbulent fluctuations can provide additional internal degrees of freedom and change the polytropic index [ Roussev et al ., ]. Slow magnetoacoustic waves, on the other hand, can change the polytropic index to be smaller than unity, which suggests that a compression of the plasma is accompanied by cooling [ Meister et al ., ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the turbulent fluctuations can provide additional internal degrees of freedom and change the polytropic index [ Roussev et al ., ]. Slow magnetoacoustic waves, on the other hand, can change the polytropic index to be smaller than unity, which suggests that a compression of the plasma is accompanied by cooling [ Meister et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…A theoretical study of Meister et al . [] shows that the value of the polytropic index is not universal constant but depends on wave modes and the plasma population in turbulent systems. Their results show that slow magnetoacoustic waves have an effective polytropic index smaller than unity near the bow shock and in some proper magnetosheath and have an effective polytropic index larger than 2 in the vicinity of the magnetopause.…”
Section: Introductionmentioning
confidence: 99%
“…Song & Thomsen (1992) studied three magnetosheath passes with a slow mode transition in front of the magnetopause, and found that two of them have the same polytropic indices with α = 1.0 ± 0.1, and the other one has a similar polytropic index with α = 1.2 ± 0.1, i.e., the observed ions are closer to isothermal than to adiabatic. The theoretical results of Meister et al (2011) showed that the effective polytropic index of an anisotropic magnetosheath plasma depends on the wave modes.…”
Section: Introductionmentioning
confidence: 99%
“…Using the double‐polytropic closure for the anisotropic magnetosheath plasma, Hau et al () showed that the magnetosheath plasma typically behaves more like quasi‐isothermal conditions (α ⊥ = 0.94 ± 0.10 and α ∥ = 1.14 ± 0.13), rather than adiabatic conditions (α ⊥ = 2 and α ∥ = 3). Pudovkin et al () and Meister et al () examined the thermodynamic properties for magnetized anisotropic plasma using the anisotropic magnetohydrodynamics (MHD) with the double‐adiabatic law and suggested that the effective polytropic index, which is characterized by the relationship between the total thermal energy and the number density of the plasma in their studies, depends both on the characteristics of the plasma flow and on the temperature anisotropy. Using the polytropic relation and Bernoulli's theorem, Pang et al () examined the polytropic indices for magnetosheath ions estimated along the same streamline and found that their probability distribution has a major peak near 1 (that is, quasi‐isothermal process) with a minor peak near 0 (that is, quasi‐isobaric process).…”
Section: Introductionmentioning
confidence: 99%